2019
DOI: 10.1186/s40463-019-0347-6
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea in patients with laryngeal cancer after supracricoid or vertical partial laryngectomy

Abstract: Objective To investigate whether partial laryngectomy is a risk factor for obstructive sleep apnea (OSA) and the effect of different partial laryngectomy methods on OSA. Method A prospective study was carried out involving 40 patients who underwent supracricoid partial laryngectomy (SCPL) (24) or vertical partial laryngectomy (VPL) (16) for carcinoma of the larynx. Apnea-hypopnea index (AHI) and oxygen saturation determined by polysomnography (PSG), Epworth sleepiness s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…Similarly, several factors may contribute to the increased incidence of OSA in patients treated for larynx or tongue cancer with surgery. Ouyang et al [28] studied the anatomical changes in patients with partial laryngectomy and OSA. The authors showed that after partial laryngectomy, the thyroid cartilage, which maintains open the laryngeal cavity, is replaced by soft tissue that collapses more frequently during inhalation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, several factors may contribute to the increased incidence of OSA in patients treated for larynx or tongue cancer with surgery. Ouyang et al [28] studied the anatomical changes in patients with partial laryngectomy and OSA. The authors showed that after partial laryngectomy, the thyroid cartilage, which maintains open the laryngeal cavity, is replaced by soft tissue that collapses more frequently during inhalation.…”
Section: Discussionmentioning
confidence: 99%
“…Authors diagnosed OSA ranging from mild to severe in 50% of patients (Table 2). Two studies analysed the incidence of OSA in patients with head and neck cancer treated only with surgery [22,28]. These studies included only laryngeal function preservation surgery and found an OSA incidence near 85%.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In one study, patients who underwent partial laryngectomy for carcinoma of the larynx showed during laryngoscopy narrowed retro-palatal and retro-lingual space post-operatively. OSA was more severe in parallel with the residual narrow airway 55 . It is therefore concluded that after surgery/radiotherapy of this type of tumours, a sleep study should be performed routinely.…”
Section: Obstructive Sleep Apnoea In Patients With Head and Neck Cancermentioning
confidence: 93%